Profiling ambivalence in the context of nonsuicidal self-injury - Gray, Nicole; Uren, Hannah; Pemberton, E.; Boyes, Mark (WILEY, 2023)
Background: We aimed to identify profiles of ambivalence among individuals with a history of non-suicidal self-injury (NSSI) and tested whether profiles differed across various theoretically informed constructs: NSSI-related characteristics, cognitive (outcome expectancies, self-efficacy to resist NSSI), emotional (psychological distress, difficulties in emotion regulation), personality, and incentives to engage/not engage in NSSI. Methods: Individuals with a lifetime history of NSSI (n = 224) reported the extent to which they wanted to and did not want to engage in NSSI and completed well-validated measures of the constructs of interest. Results: Latent profile analysis indicated four ambivalence profiles (avoid: n = 39; moderately ambivalent: n = 85; highly ambivalent: n = 30; approach: n = 70). The profiles differed across a number of NSSI-related characteristics, cognitive, emotional, and incentive-related variables. Differences between the ambivalence profiles and the avoid/approach profiles varied across constructs. For example, the ambivalence and approach profiles were similar for NSSI-related outcome expectancies, but the ambivalence and avoidance profiles were similar for self-efficacy to resist NSSI. Conclusion: Findings highlight variation between the desire to engage or not engage in NSSI that are consistent with the notion of ambivalence. Understanding these differences may allow for a more person-centered approach in treatment for NSSI.